Social Media Use, Emotion Regulation, and Social Anxiety Among Adolescents: A Systematic Literature Review - I Made Agus Madya Wiraputra (Journal of Creative Power and Ambition (JCPA), 2026)
This systematic literature review synthesises recent evidence (2015–2025) on the interrelations among social media use, emotion regulation, and social anxiety in adolescents, and examines the extent to which emotion regulation operates as a mechanism linking social media use to social anxiety. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2020) guideline, peer-reviewed studies and evidence syntheses were identified through structured searches of major databases and screened against predefined eligibility criteria. The synthesis indicates that the association between the sheer quantity of social media use and social anxiety is generally weak and inconsistent, whereas problematic and appearance-oriented patterns of use show more robust positive associations. Emotion regulation emerges as a consistent thread: maladaptive strategies—expressive suppression, rumination, upward social comparison, and feedback- and reassurance-seeking—appear to mediate or amplify the relationship between social media engagement and social-evaluative anxiety, whereas adaptive strategies such as cognitive reappraisal and higher emotional intelligence function as protective factors. The relationship is best characterised as transactional rather than unidirectional. Methodological limitations of the underlying evidence base—dominated by cross-sectional designs and heterogeneous measurement—constrain causal inference. Implications for school counselling, digital-literacy education, and emotion-regulation interventions are discussed, together with a research agenda emphasising longitudinal and intensive-longitudinal designs